Agentes anticoagulantes e antiplaquetários evitam a trombose aguda do enxerto, no transplante renal?: uma metanálise de estudos de séries de casos - Silva, Rodrigo Guerra da [UNESP] (2015)
It is expected that renal graft thrombosis occurs in 1-6% of kidney transplants, and that graft loss usually arises from that event. Anticoagulants and antiplatelet agents could serve as pharmacological measures to prevent it, but high-quality evidence for its benefits are lacking at this moment. Thus, we evaluated the efficacy and safety of these agents in reducing the rate of thrombosis in renal grafts through analysis of data obtained from case series studies. Methods: A literature review was conducted, in the main electronic health-related databases (MEDLINE, EMBASE and LILACS), to identify all available case series studies on the use of anticoagulants and/or antiplatelet agents in preventing graft thrombosis in renal transplantation. Data on events of interest were pooled and analyzed on a proportional meta-analysis. The presence of statistical significance in the comparisons was established when the 95% confidence intervals (95% CI) obtained for each tested intervention did not present overlapping. Results: 21 case series were included, from 7,160 titles originally identified in the databases. A total of 3,246 patients were analyzed (1,718 treated with antiplatelet and/or anticoagulant agents and 1,528 individuals as untreated controls). Allograft thrombosis occurred in 7.24% (95% CI 3.45 to 12.27%) of patients that received no intervention, compared with 3.38% (95% CI 1.45 to 6.08%) of who used only anticoagulant, 1.20% (95% CI 0.60 to 2.10%) of those in use only of aspirin and 0.47% (95% CI 0.001 to 1.79%) of those who received aspirin + anticoagulants. As such, there was a statistically significant difference showing a reduction in the occurrence of thrombosis, only in patients receiving aspirin or aspirin + anticoagulants, compared to untreated controls. The rate of complications related to bleeding was statistically higher with use of anticoagulants (28.00%; 95% CI 15.40 to 42.70%)...